2016
DOI: 10.4028/www.scientific.net/kem.704.406
|View full text |Cite
|
Sign up to set email alerts
|

Shaping Strategies for Porous Ti Fabrication throughout Colloidal Chemistry

Abstract: Aimed by reducing the total cost of products, powder metallurgy (PM) processing of Ti is a subject of high interest. However, using of conventional PM techniques presents difficulties due to the intrinsic characteristics of Ti, like low strain ability, and high reactivity, which lead to low compressibility. Moreover, Ti powders with small particle size are difficult to process by conventional PM techniques as they present a lower compressibility and also a poor flowability. On the other hand, the colloidal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Ti slurries were formulated by incorporating ammonium bicarbonate as the porogen agent and MC as the shaping additive. Dispersion of the Ti powders in water has been previously reported by authors in terms of zeta potential and rheological behavior using an anionic and a cationic dispersant as well as bare powders [ 26 , 27 ]. On those papers, the Krieger Dougherty’s rheological model showed that using PEI (cationic dispersant) in the slurries formulation the values of maximum packing density were as high as 74% while the use of an anionic polyelectrolyte (Polyacrylic Acid-PAA, Mw = 2000, Acros) generated a maximum packing density value of 56%.…”
Section: Resultsmentioning
confidence: 99%
“…Ti slurries were formulated by incorporating ammonium bicarbonate as the porogen agent and MC as the shaping additive. Dispersion of the Ti powders in water has been previously reported by authors in terms of zeta potential and rheological behavior using an anionic and a cationic dispersant as well as bare powders [ 26 , 27 ]. On those papers, the Krieger Dougherty’s rheological model showed that using PEI (cationic dispersant) in the slurries formulation the values of maximum packing density were as high as 74% while the use of an anionic polyelectrolyte (Polyacrylic Acid-PAA, Mw = 2000, Acros) generated a maximum packing density value of 56%.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous works [6,7], the dispersion and stabilization conditions of Ti powders in aqueous media was used. A solid content of 50 vol.% prepared with 1 wt.% of PEI as dispersant was selected to formulate of the Ti slurries.…”
Section: Figure 1 Scheme Of the Slurry With MC As Gelling Agent And Bc As Porogenmentioning
confidence: 99%